2011
DOI: 10.1111/j.1439-0426.2011.01751.x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding habits of ocellate spot skate, Okamejei kenojei (Müller & Henle, 1841), in coastal waters of Taean, Korea

Abstract: The feeding habits of Okamejei kenojei were studied using 592 specimens collected in the coastal waters of Taean, Korea from April 2008 to March 2009. O. kenojei is a bottom-feeding carnivore that consumes mainly shrimp, fishes, and crabs. Its diet also includes small quantities of amphipods, mysids, cephalopods, euphausiids, copepods, isopods, and polychaetes. The total length (TL) of individuals in this study ranged from 8.2 to 49.0 cm. Cluster analysis based on %IRI (index of relative importance) identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 28 publications
(53 reference statements)
0
7
0
1
Order By: Relevance
“…Okamejei kenojei has considerable economic value in Korea and Japan (Ishihara, 1990;Ishihara et al, 2009;Baeck et al, 2011). Domingues et al (2018) suggested that management and conservation policies for shark and ray fisheries should include information on genetic diversity.…”
mentioning
confidence: 99%
“…Okamejei kenojei has considerable economic value in Korea and Japan (Ishihara, 1990;Ishihara et al, 2009;Baeck et al, 2011). Domingues et al (2018) suggested that management and conservation policies for shark and ray fisheries should include information on genetic diversity.…”
mentioning
confidence: 99%
“…According to Gerking (), the diets of syntopic species in different genera are not expected to overlap, plus the availability of feeding resources influences the number of individuals and species that can coexist in a given habitat (Piet, Pfisterer, & Rijnsdorp, ; Schuckel, Sell, Kroncke, & Reiss, ). Spatial, temporal and/or ontogenetic segregation among the feeding resources are common strategies developed by species to avoid intra and interspecific competition (Baeck, Park, Choi, Hug, & Park, ; Lomiri, Scacco, Mostarda, & Andaloro, ; Young et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The East China Sea, located across both temperate and subtropical zones and bound by China, South Korea and Japan, is near the southern border of the distribution range of D. chinensis. Skates are caught by Japanese and Korean trawlers, and are commercially important fish in the East China Sea and adjacent waters (Baeck, Park, Choi, Huh, & Park, 2011;Hara, Furumitsu, & Yamaguchi, 2014;Ishihara, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Skates are caught by Japanese and Korean trawlers, and are commercially important fish in the East China Sea and adjacent waters (Baeck, Park, Choi, Huh, & Park, 2011;Hara, Furumitsu, & Yamaguchi, 2014;Ishihara, 1990).…”
Section: Introductionmentioning
confidence: 99%